Internal migration, urbanization and poverty in Asia dynamics and interrelationships - Jayanthakumaran, Kankesu; Verma, Reetu; Wan, Guanghua 1961-; Wilson, Edgar J. (Springer Open, 2019)
Asia's recent demographic transitions and rural-urban structural transformations are extraordinary and involve complexities that require in-depth study. The chapters within this volume examine those complexities using a range of traditional and nontraditional measures--such as multidimensional poverty, gaps, and polarization--to arrive at the conclusion that poverty is now an urban issue. This volume offers an essential resource for economic policy makers and students of development economics to understand the interrelationships between internal migration, urbanization, and poverty in Asia, paving the way for the improved management of internal migration, and disadvantaged and vulnerable populations. Kankesu Jayanthakumaran is a Senior Lecturer at the University of Wollongong, Australia.
Keywords: Armut; Binnenwanderung; Verstädterung; Asien; Rural-urban migration / Asia; Urbanization / Asia; Poverty / Asia; Poverty; Rural-urban migration; Urbanization; Asia; Konferenzschrift -- 2016 -- Siem Reap